PELATIHAN MEDIA PEMBELAJARAN DARING PADA MAHASISWA PPG PRAJABATAN BIDANG STUDI EKONOMI - Rachmat Efendi; Rifki Arifin; Yoan Tatang Pratiwi; Sofiyan Pradana Kusuma (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
In this community service activity, the team provided seminars and training in making interactive and innovative online learning media to PPG Pre-Service Students in the Field of Economics Study Wave 1, University of Jember (UNEJ). In the method used, it starts from analyzing the situation and needs, then identifying problems, followed by determining goals, ending with a problem-solving plan. In the implementation of this activity, it was carried out twice, the first online meeting using google meet and the second meeting was training in the classroom meeting directly with students. Based on the results of the service that has been carried out, it can be concluded that 1) the participants who participated in this service event were limited to 15 of the PPG Pre-service students in the field of Economics Study Wave 1 of the University of Jember (UNEJ); 2) the students who took part in the training felt happy with this kind of activity, because the process was delivered not only online, but offline and hands-on practice; 3) in the hands-on session, students can discuss and ask questions about developing interactive and innovative online learning media